Endothelin antagonist as add-on treatment for proteinuria in diabetic nephropathy: is there light at the end of the tunnel? - Ritz, Eberhard; Wenzel, René R. (Journal of the American Society of Nephrology, 2011)
After the seminal discovery by Yanagisawa et al. [1][1] of the endothelial cell-derived vasopressor endothelin-1 (ET) and eventually the identification of two other isoforms, inhibitors of the ET receptors (ETA, ETB1, and ETB2) were high on the list of therapeutic drugs for the pharmaceutical
Gesehen am 16.09.2022